The border made city: six vignettes from, and a run in, Chelas, Lisbon - Tulumello, Simone (2022)
The aim of this article is to capture the idea of the urban border by painting a tour of Chelas — a geographically central district but mentally located by Lisboners in a peripheral space made up of representations of poverty, decay, danger and deviance. For that purpose, the piece is crafted with data from 2011, in the form of notes and photos collected at the time, but also with a different type of “data”, that is, collected through another, less common, form of (participant) observation: running. Through running, I have kept experiencing Chelas, observing its change in time and feeling its complex topography. By reflecting on my experience as runner in Chelas as a flow connecting the six vignettes that follow, I will try to think urban running as a way through, and beyond, the border.